ANALISIS TINGKAT KECERDASAN EMOSI MAHASISWA MURNI DAN MAHASISWA BEKERJA DALAM MENGIKUTI KULIAH ONLINE - Musnizar Safari (Jurnal Ilmiah Pendidikan Anak (JIPA), 2021)
Each student hopes to follow the learning process well so that the final results can be good and satisfied grades. The learning process conducted is not like usual such as online learning, it has caused a variety of students’ emotions. This aim of this study is to determine the students’ level of emotional intelligence who follow the online class is about 43 PG-PAUD students through the distribution of an emotional intelligence scale. The method used is descriptive qualitative and the data is analyzed by percentage technique. The results showed that 67.4% of PG-PAUD students' emotional intelligence levels were in the medium category, and the other 32.6% were in the low (11.6%) and high (21%). Puring students dominate in the category of low and high emotional intelligences’ levels than working students who dominate in the category of moderate emotional intelligences’ levels. The difference level of emotional intelligence between puring and working students is only 0.8% in average. The factors that cause pure students to dominate the level of emotional intelligence in the low and high categories: 1) age who are in transition (19 – 22 years old) from late adolescence to early adulthood; and 2) the difficulty of the internet network in the student's domicile area which causes anxiety when participate in the online learning process. Key words: smart, emotion, learning process, working students, online